Green Hydrogen Production in Libya: Opportunities for Harnessing Solar Energy to Achieve Sustainable Development and Economic Diversification - Ablqasim Bassam; Rodwan Elhashmi; Albahloul Abdulghafur (Journal of Scientific and Human Dimensions, 2025)
Libya faces a significant challenge in transitioning from near-total dependence on fossil fuels to sustainable energy systems. This study aims to explore the feasibility of producing and utilizing green hydrogen as a clean energy alternative, leveraging Libya's abundant solar resources, which average 4.94 kWh/m²/day in Tripoli and up to 6 kWh/m²/day in other regions. Using the HOMER Pro software, a system was designed to produce 100 kg/day of green hydrogen through solar-powered electrolysis, with seasonal adjustments to increase production to 150 kg/day during peak solar months (April - October). The proposed system includes solar panels with a capacity of 4656 kW, lithium-ion battery storage with a capacity of 9530 kWh, and an electrolyzer with a capacity of 2000 kW, resulting in an annual production of 36,498 kg. Economic analysis reveals a levelized cost of energy (LCOE) of $0.42/kg, which is competitive with global standards, and a total net cost of $12.78 million. The project highlights Libya's potential to reduce carbon emissions, diversify its economy, and position itself as a key supplier to European markets. The study also addresses challenges such as political stability, infrastructure deficits, and the need for legislative frameworks, alongside recommendations for investment and an overview of major green hydrogen projects in North Africa and worldwide
Keywords: green hydrogen; solar energy; Electrolysis; Sustainable Development